Gaining Motivation on English Learning for Special Need Students Using Flashcards, Foldable Books and Posters in EFL Context - Suhartini Syukri; Isna Humaera (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
Teaching special needs students becomes more challenging and frustrating. Moreover, some SLB in Kendari nowadays have not been facilitated by suitable learning media, particularly in EFL context. This study describes the research that sought to understand if the teaching media electronic or not, using flashcards, foldable books, and posters, is under the necessities of deaf and hard hearing students. This question becomes the primary goal of the investigation, and its enlighten is divided into three specific goals. They are, finding out the effects of the media used in assisting special need students and EFL teacher in the class; helping them in communication and comprehending the teaching materials especially in vocabulary English class; and gaining EFL teacher’s and special need students’ motivation in teaching and learning process utilizing the media. This study used qualitative by single case study design, which was conducted about six months in 2018. Five students by deaf and hard hearing impairment of SLB-F Mandara (special private junior high school) are as the sample of this study. The observation list and depth-interview were utilized in data collection. After doing some interventions, the data analysis used data reduction, data display, and conclusion. The results showed that by intervention and utilizing diverse media by flashcards, foldable books and posters could ultimately gain teacher’s and students’ motivation in the EFL context.